Balaghah-Informed Examination of Dilalah Jumlah Ismiyyah and Filiyyah for Holistic Quranic Understanding - Mohammad Irfan Farraz Haecal; Edi Komarudin; Wildan Taufiq (Senarai: Journal of Islamic Heritage and Civilization, 2025)
This article explores the critical role of Dilalah Jumlah Ismiyyah (implications of nominal quantity) and Dilalah Jumlah Fi'liyyah (implications of verbal quantity) in the profound interpretation of the Holy Qur'an. As the foundational text of Islam, the Qur'an necessitates a comprehensive linguistic and rhetorical understanding to fully grasp its spiritual and practical guidance. We argue that analyzing the quantitative nuances within nominal (ism) and verbal (fi'il) structures is indispensable for unveiling the divine messages. The study delves into how the singular or plural usage of nouns and verbs influences meaning, conveying concepts ranging from God's absolute oneness to the collective responsibilities of humanity. Furthermore, it highlights the intricate relationship between Ismiyyah and Fi'liyyah, demonstrating how they mutually reinforce semantic depth and rhetorical impact within Qur'anic discourse. By integrating Balaghah (Arabic rhetoric) and considering the broader historical, cultural, and spiritual contexts of revelation, this research proposes a refined approach to Qur'anic exegesis. Ultimately, a meticulous examination of quantitative dilalah enriches our comprehension of the Qur'an's multifaceted meanings and its timeless ethical and moral teachings.